AKUNTABILITAS, TRANSPARANSI DAN PARTISIPASI PENGELOLAAN DANA DESA DI KECAMATAN AMFOANG UTARA KABUPATEN KUPANG - Tuati, Nonce Farida; Manuain, Deetje Wieske; Usman, Hapsa (Universitas Sam Ratulangi, 2023)
The purpose of this kamislot study was to determine and analyze the accountability of village fund management in five villages in The North Amfoang District. The results of this study are expected to be one part of the development of accounting science and can be a reference in solving problems that are being faced by various types of organizations in Indonesia, such as the government, especially village governments, universities, and other social organizations. Respondents in this study were sub-district and village officials which included: The sub-district head, sub-district secretary, village head, village secretary, village treasurer, village consultative body (BPD), hamlet head, head of RT, community leaders, religious leaders, traditional and community leaders. Data collection was carried out using a semi-structured interview method by asking oral questions directly to research informants. The data analysis method used is descriptive qualitative. The results showed that five villages in North Amfoang District had implemented the principles of accountability, transparency, and participation in managing village funds. In general, the principles of accountability, transparency, and participation have been implemented but several indicators have not been implemented properly.